2019
DOI: 10.1111/sms.13506
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness modulates the proportions of monocytes and T helper subsets in lean and obese men

Abstract: Funding informationWe are grateful to the Brazilian agencies Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) -Finance Code 001, CAPES (CAPES-PNPD -23038007200/11-08) and Conselho Nacional de Desenvolvimento Cientifico e Tecnológico (CNPq) for financial support. PDL, AP, and PRTR also thank CNPq for fellowships.This study investigated the peripheral frequency of monocytes, CD4 + T cell subsets and the systemic levels of cytokines in lean and obese men with different levels of cardiorespirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…The positive modulation of the PGC-1α/PPAR-γ axis observed in the molecular environment may orchestrate the anti-inflammatory responses observed in the peripheral/systemic blood after acute aerobic exercise explains the circulating IL-6 and IL-10 concentrations. These findings allow us to understand that beneficial peripheral responses to exercise training are modulated directly by the molecular/cellular adaptations of "individual biological machinery" and a recent study conducted by Dorneles and colleagues 53 corroborates and strengthens our hypothesis.…”
Section: Discussionsupporting
confidence: 82%
“…The positive modulation of the PGC-1α/PPAR-γ axis observed in the molecular environment may orchestrate the anti-inflammatory responses observed in the peripheral/systemic blood after acute aerobic exercise explains the circulating IL-6 and IL-10 concentrations. These findings allow us to understand that beneficial peripheral responses to exercise training are modulated directly by the molecular/cellular adaptations of "individual biological machinery" and a recent study conducted by Dorneles and colleagues 53 corroborates and strengthens our hypothesis.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, it would be interesting to study if changes in the myeloid cell distribution pattern correlate with treatment response determined by other "hard" parameters such as counts of CNS lesions and frequency of adverse events. Such study with a larger patient cohort could also account for other immune profile-modifying variables such as body mass index (BMI) or motor performance (49).…”
Section: Discussionmentioning
confidence: 99%
“…This seems to indicate that cardiorespiratory fitness (CRF) could be related with ASC regulation. Also, other studies in overweight or obese participants have reported that CRF has an inverse association with inflammation mediators in peripheral blood lymphocytes, monocytes, neutrophils, and non-classical monocytes [26][27][28]. However, given the significance of low-grade chronic inflammation in the pathogenesis of various diseases, the association between fitness and inflammation in obese patients is still unclear.…”
Section: Discussionmentioning
confidence: 99%